2017
DOI: 10.3390/molecules22111937
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Seven Components in Rat Plasma by the UPLC-MS/MS Method and Application of Pharmacokinetic Studies to SimiaoYong’an Decoction

Abstract: SimiaoYong’an Decoction (SYD) is a classical traditional Chinese prescription that is used for the treatment of gangrene, heat-clearing, detoxification and pain alleviation. We developed a sensitive ultra-performance liquid chromatography-tandem mass spectrum (UPLC-MS/MS) method for the simultaneous determination of seven major active ingredients of SYD extract (i.e., harpagide, chlorogenic acid, sweroside, loganin, liquiritin, angoroside C and harpagoside) in rat plasma. The preliminary steps in the plasma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…To date, some HPLC methods were applied in determine angoroside C in Radix Scrophulariae ( Yang et al, 2009 ; Zhang et al, 2011 ), and only one paper reported the LC-MS/MS method to determine multi-components including angoroside C in plasma after intragastric SimiaoYong′an decoction to rat ( Liu et al, 2017a ). But beyond that, no significant ADME studies have been published in the literature on angoroside C and its metabolites in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…To date, some HPLC methods were applied in determine angoroside C in Radix Scrophulariae ( Yang et al, 2009 ; Zhang et al, 2011 ), and only one paper reported the LC-MS/MS method to determine multi-components including angoroside C in plasma after intragastric SimiaoYong′an decoction to rat ( Liu et al, 2017a ). But beyond that, no significant ADME studies have been published in the literature on angoroside C and its metabolites in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…However, these components were not detectable in rat plasma after oral administration of 2500 mg/kg YGP. Considering their lower contents in YGP (for example, 0.97 μg/g for mesaconine and 2.1 μg/g for benzoylaconitine), lower absorption/bioavailability and extensive in vivo metabolism (for example, loganin , mesaconine , and fuziline ), these results are reasonable.…”
Section: Resultsmentioning
confidence: 84%
“…As a result, 14 compounds were preliminary identified, of which 10 compounds were prototypes of SMYAD, and four were metabolites (Chi et al, 2016). In addition, seven major active ingredients of SMYAD extract (i.e., harpagide, chlorogenic acid, sweroside, loganin, liquiritin, angoroside C, harpagoside) in rat plasma were detected simultaneously by a sensitive ultra-performance liquid chromatography–tandem mass spectrometry method (Liu et al, 2017a).…”
Section: Methodsmentioning
confidence: 99%